2003
DOI: 10.1002/app.12337
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic swelling behavior of pH‐sensitive anionic hydrogels used for protein delivery

Abstract: There have been many attempts to use anionic hydrogels as oral protein delivery carriers because of their pH-responsive swelling behavior. The dynamic swelling behavior of poly(methacrylic acid-co-methacryloxyethyl glucoside) and poly(methacrylic acid-g-ethylene glycol) hydrogels was investigated to determine the mechanism of water transport through these anionic hydrogels. The exponential relation M t /M ϱ ϭ kt n (where M t is the mass of water absorbed at time t and M ϱ is the mass of water absorbed at equil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(142 citation statements)
references
References 27 publications
6
135
0
Order By: Relevance
“…It was found that the solvent transport mechanism became non-Fickian (more relaxation-controlled) as gel ionisation became prominent. As discussed earlier by Peppas et al [29,31,32], the dynamic swelling behaviour of hydrogels is dependent on the relative contribution of penetrant diffusion and polymer relaxation. In the ionic hydrogels the ionisation of functional groups may control the water diffusion process, thus affecting the relative magnitude of diffusion and relaxation times [29,42].…”
Section: Case III (Or Anomalous Diffusion Non-fickian Diffusion)mentioning
confidence: 80%
See 2 more Smart Citations
“…It was found that the solvent transport mechanism became non-Fickian (more relaxation-controlled) as gel ionisation became prominent. As discussed earlier by Peppas et al [29,31,32], the dynamic swelling behaviour of hydrogels is dependent on the relative contribution of penetrant diffusion and polymer relaxation. In the ionic hydrogels the ionisation of functional groups may control the water diffusion process, thus affecting the relative magnitude of diffusion and relaxation times [29,42].…”
Section: Case III (Or Anomalous Diffusion Non-fickian Diffusion)mentioning
confidence: 80%
“…The mechanism of water transport in a swelling hydrogel is greatly affected by many factors, such as equilibrium water content, chemical composition of the hydrogel, swelling rate, etc. [30,32]. In general, three models are used to describe transport phenomena into polymer networks [33][34][35][36][37].…”
Section: Swelling Kinetics Of Hydrogel Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the swelling processes of the gels are described from the kinetic point of view by the Peppas equation [28][29][30][31] (Equation (2)): (2) This equation allows to calculate the exponent n that indicates the water (or other species) diffusion mechanism (Fickian or non-Fickian) and the diffusion constant k. This equation is not applicable in our case, due to the complexity of the process and changing gel morphology. If we still try to apply this equation, we get very low n-values, which do not correspond to the diffusion mechanism.…”
Section: 7mentioning
confidence: 99%
“…Peppas group [32][33][34][35] studied the drug delivery from a polymeric film or matrix into solution and found it obeyed to the following equation:…”
Section: Resultsmentioning
confidence: 99%